2019
DOI: 10.1039/c9ra01145e
|View full text |Cite
|
Sign up to set email alerts
|

Formation of disk-like micelles of triblock copolymers in frustrating solvents

Abstract: Self-assembly of amphiphilic triblock copolymers in a frustrating solvent system leads to the formation of various low-curvature micellar structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Nevertheless, particles formed through both CDSA and rod‐coil methods usually possess densely packed or crystalline core segments, imposing constraints on molecular loading capabilities and consequently their potential applications as drug delivery systems, despite their favourable 2D morphology. On the other hand, discs made from non‐crystalline polymers often demand intricate self‐assembly conditions in solution, limiting their applicability [17] . Currently, the exploration of nanodiscs with stimuli‐responsive properties is still in its infancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, particles formed through both CDSA and rod‐coil methods usually possess densely packed or crystalline core segments, imposing constraints on molecular loading capabilities and consequently their potential applications as drug delivery systems, despite their favourable 2D morphology. On the other hand, discs made from non‐crystalline polymers often demand intricate self‐assembly conditions in solution, limiting their applicability [17] . Currently, the exploration of nanodiscs with stimuli‐responsive properties is still in its infancy.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, discs made from non-crystalline polymers often demand intricate self-assembly conditions in solution, limiting their applicability. [17] Currently, the exploration of nanodiscs with stimuli-responsive properties is still in its infancy. However, the incorporation of stimuli-responsive characteristics into nanomaterials affords them controlled and on-demand changes to properties and functionality, which is particularly valuable in drug delivery applications.…”
mentioning
confidence: 99%
“…Qiu and co-workers used their previously discussed triblock terpolymer PS 580 - b -PB 660 - b -P2VP 920 in an acetone:cyclohexane solution (65 : 35 v/v) to generate disc-like micelles capable of perforating in the centre to yield toroidal micelles with various hole sizes. 65 Pochan, Wooley and co-workers showed the first instance of stable and reproducible toroidal self-assemblies from amphiphilic triblock terpolymers (PAA 66 - b -PMA 93 - b -PS 66 ) by manipulating the PAA block using oppositely charged divalent counterions. 135,136 The polymer assembly itself proceeded via the addition of water to a THF solution (4 : 1 THF:water for toroid formation) in the presence of ethylenediamine (EDDA, with a ratio of amine:acid between 0.5 : 1 and 1 : 1) and subsequent removal of THF by evaporation.…”
Section: Polymer Nanoscale Toroidsmentioning
confidence: 99%
“…64 Qiu and co-workers developed a strategy towards lowcurvature micellar structures by assembling amphiphilic block copolymers in a mixture of polar and nonpolar (near-)theta solvents. 65 The self-assembly of PS-b-PB-b-P2VP triblock terpolymers at different solvent ratios resulted in both toroidal and disc geometries. A polymer solution in THF was injected into a mixture of acetone and cyclohexane.…”
Section: Direct(ed) Self-assembly In Solutionmentioning
confidence: 99%
“…This morphology evolution is associated with the inversion of the core and corona of micelles, which is induced by enhanced solubility of core-forming chains or lowered solubility of corona-forming chains. [90][91][92][93] Zhang et al reported the sphere-to-toroid transition of a pH-sensitive ABC triblock copolymer poly(N,Ndimethylacrylamide)-block-polystyrene-block-poly[N-(4-vinylbenzyl)-N,N-dibutylamine] (PDMA-b-PS-b-PVBA) assembly system through the in-to-out switch strategy of the core-forming C block (PVBA) in solution (Figure 8a). [91] The ABC triblock copolymer self-assembles into spherical micelles with a core-shell-corona structure (Figure 8b).…”
Section: In-to-out Switch Of Micellesmentioning
confidence: 99%